Super-Eddington Mechanical Power of an Accreting Black Hole in M83 - Soria, Roberto; Long, K.; Blair, W.; Godfrey, L.; Kuntz, K.; Lenc, E.; Stockdale, C.; Winkler, P. (The American Association for the Advancement of Science, 2014)
Mass accretion onto black holes releases energy in the form of radiation and outflows. While the radiative flux cannot substantially exceed the Eddington limit, at which the outgoing radiation pressure impedes the inflow of matter, it remains unclear whether the kinetic energy flux is bounded by this same limit. Here we present the detection of a radio/optical structure, powered by outflows from a non-nuclear black hole. Its accretion disk properties indicate that this black hole is less than 100 solar masses. The optical/IR line emission implies an average kinetic power of 3 × 10 40 erg second-1, higher than the Eddington luminosity of the black hole. These results demonstrate kinetic power exceeding the Eddington limit over a sustained period, which implies greater ability to influence the evolution of the black hole’s environment.